A REVIEW ON THE ECONOMIC IMPACT AND GROWTH TRENDS OF PENAEUS MONODON AQUACULTURE - Ramya R; Thangasubha T; L Ashwini; S.C. Subha (The Bioscan, 2025)
Prawns, a group of economically valuable crustaceans commonly referred to as shrimp in trade, are widely consumed around the world and known by various local names such as Chingri, Ghinga, Kolambi, Sungata, Chemen, and Shetli. Celebrated globally for their delicate flavor, prawns are considered a culinary delicacy. They inhabit coastal areas, lakes, estuaries, and creeks, with the majority of production originating from marine environments. India ranks second only to the United States in prawn production, with Penaeus monodon (giant tiger prawn) comprising nearly 90% of the country's crustacean yield. Although prawn farming has been practiced for a long time in India and other Asian countries, it remained a relatively neglected branch of fisheries for many years. Traditionally, most prawn catches came directly from the wild, often involving juvenile specimens. In recent decades, declining wild stocks and growing demand have prompted increased attention from fisheries departments toward scientific and technical advancements in prawn aquaculture. Shrimp farming has since become a significant contributor to India’s seafood exports, generating annual foreign exchange revenues estimated between ₹70–₹80 crores. This review explores the economic growth, cultural practices, and market dynamics of Penaeus monodon farming in India.